Effects of Episodic Future Thinking on Delay and Effort Discounting - Peck, Sara; Madden, Gregory J. (The Psychological record, 2023)
The discounting of costly rewards is robustly correlated with maladaptive tendencies like substance use, relapse, and poor health habits. Because of this, many laboratory-based interventions have been developed to reduce discounting. Most of these interventions aim to reduce discounting of delayed rewards (delay discounting) but many desirable outcomes in daily life also require effort. The present experiment sought to evaluate the efficacy of episodic future thinking (EFT) to reduce effort discounting. EFT has proven effective in reducing delay discounting, but has not been evaluated as a means of reducing effort discounting. We also evaluated the influence of different types of examples provided to participants during the EFT and control tasks. In a 2x2 between-groups design, participants were randomly assigned to an EFT or control group, combined with one of two example-type conditions. Participants completed the EFT or control tasks, followed by delay- and effort-discounting tasks. As in prior studies, EFT significantly reduced delay discounting, but the effect on effort discounting fell short of significance. Example type did not affect these outcomes.